Priests of My People Levitical Paradigms for Early Christian Ministers - Stewart, Bryan A.; Stewart, Bryan A. (Peter Lang, 2015)
This book offers an innovative examination of the question: why did early Christians begin calling their ministerial leaders (S0(Bpriests(S1 (B(using the terms hiereus/sacerdos)? Scholarly consensus has typically suggested that a Christian (S0(Bpriesthood(S1 (Bemerged either from an imitation of pagan priesthood or in connection with seeing the Eucharist as a sacrifice over which a (S0(Bpriest(S1 (Bmust preside. This work challenges these claims by exploring texts of the third and fourth century where Christian bishops and ministers are first designated (S0(Bpriests(S1(B: Tertullian and Cyprian of Carthage, Origen of Alexandria, Eusebius of Caesarea, and the church orders Apostolic Tradition and Didascalia Apostolorum. Such an examination demonstrates that the rise of a Christian ministerial priesthood grew more broadly out of a developing (S0(Breligio-political ecclesiology(S1(B. As early Christians began to understand themselves culturally as a unique polis in their own right in the Greco-Roman world, they also saw themselves theologically and historically connected with ancient biblical Israel. This religio-political ecclesiology, sharpened by an emerging Christian material culture and a growing sense of Christian (S0(Bsacred space(S1(B, influenced the way Christians interpreted the Jewish Scriptures typologically. In seeing the nation of Israel as a divine nation corresponding to themselves, Christians began appropriating the Levitical priesthood as a figure or (S0(Btype(S1 (Bof the Christian ministerial office. Such a study helpfully broadens our understanding of the emergence of a Christian priesthood beyond pagan imitation or narrow focus on the sacrificial nature of the Eucharist, and instead offers a more comprehensive explanation in connection with early Christian ecclesiology.s